Morinda officinalis polysaccharide enable suppression of osteoclastic differentiation by exosomes derived from rat mesenchymal stem cells. (31st December 2022) - Wu, Peiyu; Jiao, Feng; Huang, He; Liu, Donghua; Tang, Wang; Liang, Jie; Chen, Wen
Abstract: Context: Morinda officinalis F.C. How. (MO) (Rubiaceae) can strengthen bone function. Objective: To examine the functional mechanism and effect of MO polysaccharides (MOPs) in rats with glucocorticoid-induced osteoporosis (GIOP). Materials and methods: Rats with GIOP were treated with 5, 15 or 45 mL/kg of MOP [ n  = 15 for each dose, intraperitoneal (i.p.) injection every other day for 8 weeks]. The body weight of rats and histomorphology of bone tissues were examined. Bone marrow mesenchymal stem cells (BMSCs)-derived exosomes (Exo) were collected and identified. Bone marrow-derived macrophages (BMMs) were induced to differentiate into osteoclasts and treated with BMSC-Exo for in vitro studies. Results: MOP reduced the body weight (5, 15, or 45 mg/kg MOP vs. phosphate-buffered saline: 8%, 15% and 25%, p  < 0.01), elevated the bone volume to tissue volume (BV/TV), mean trabecular thickness (Tb.Th), mean trabecular number (Tb.N) and mean connectivity density (Conn.D) (40–86%, p  < 0.01), decreased the mean trabecular separation/spacing (Tb.Sp) (22–37%, p  < 0.01), increased the cortical bone continuity (35–90%, p  < 0.01) and elevated RUNX family transcription factor 2 and RANK levels (5–12%, p  < 0.01), but suppressed matrix metallopeptidase 9 and cathepsin K levels (9–20%, p  < 0.01) in femur tissues. BMSC-Exo from MOP-treated rats (MOP-Exo) suppressed osteoclastic differentiation and proliferation of BMMs. The downregulation of microRNA-101-3p (miR-101-3p) or the upregulation of prostaglandin-endoperoxide synthase 2 (PTGS2) blocked the functions of MOP-Exo. Discussion and conclusions: MOP inhibits osteoclastic differentiation and could potentially be used for osteoporosis management. This suppression may be enhanced by the upregulation of miR-101-3p or the inhibition of PTGS2.